2009
DOI: 10.1128/jcm.00098-09
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Plasmid-Mediated KPC-Producing Klebsiella pneumoniae in Ottawa, Canada: Evidence of Intrahospital Transmission

Abstract: Klebsiella pneumoniae isolates from three patients admitted to the Ottawa Hospital, a 1,040-bed teaching hospital, were found to contain the plasmid-borne K. pneumoniae carbapenemase (KPC)-producing bla gene ( bla KPC ) . There was evidence of person-to-person transmission for two patients. Screening of 186 clinical isolates revealed no additional bla KPC -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…In 2008, 10 isolates of K. pneumoniae were referred to the Ontario Public Health Laboratories for further testing. 11,12 The initial results of susceptibility testing of 1 of the 10 isolates using an automated method suggested that the organism was susceptible to meropenem. However, the initial results of testing using routine clinical laboratory methods showed general resistance to all lactams, with complete or intermediate resistance to meropenem, which raised the possibility of KPC production.…”
Section: Diagnosismentioning
confidence: 99%
“…In 2008, 10 isolates of K. pneumoniae were referred to the Ontario Public Health Laboratories for further testing. 11,12 The initial results of susceptibility testing of 1 of the 10 isolates using an automated method suggested that the organism was susceptible to meropenem. However, the initial results of testing using routine clinical laboratory methods showed general resistance to all lactams, with complete or intermediate resistance to meropenem, which raised the possibility of KPC production.…”
Section: Diagnosismentioning
confidence: 99%
“…In particular, K. pneumoniae isolates producing KPC carbapenemases (KPC-Kp) are spreading at an alarming rate in North and South America, the Caribbean, Europe, Israel, and Asia (6,7,15,17,18). Like ESBL producers, KPC-Kp are often resistant to quinolones and aminoglycosides (6).…”
mentioning
confidence: 99%
“…terdiri dari 3 jenis porin yaitu OmpK35, OmpK36, dan OmpK37 (Hernandez-Alles et al, 1999;Kaczmarek et al, 2006). Porin OmpK35 dan OmpK36 berperan penting pada penetrasi antibiotik ke dalam sel, sehingga hilangnya porin OmpK35 dan OmpK36 dapat menyebabkan resistensi bakteri terhadap carbapenem (Doumith et al, 2009;Goldfarb et al, 2009;Kontopoulou et al, 2010).…”
Section: H a S I L D A N P E M B A H A S A Nunclassified